INTEGRASI ASESMEN MULTILITERASI DALAM PEMBELAJARAN MENDALAM IPAS : ANALISIS OBSERVASI KELAS PADA MATERI METAMORFOSIS - Risa Septiana; Intan Sari Rufiana; Sri Rahayuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of multiliteracy assessment in deep learning-based IPAS instruction on metamorphosis material in a third-grade classroom. Using a qualitative descriptive-analytic case study approach, the research explores a single learning cycle implemented through the Problem Based Learning (PBL) model at SD Negeri 4 Kaumrejo. Data were collected through document analysis, video-based observation, and semi-structured interviews, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that multiliteracy assessment is substantially integrated, as reflected in the presence of various literacy modes linguistic, visual, oral, spatial, digital, critical, and social across learning phases, with peak integration during investigation and presentation activities. Authentic assessments such as concept maps and dioramas effectively capture students’ multimodal competencies. However, gaps remain in the explicit assessment of digital and critical literacy, assessment differentiation, and structured student reflection. The study highlights the need for more comprehensive and specific rubrics to optimize multiliteracy assessment practices in primary education.